2022
DOI: 10.1002/cpz1.351
|View full text |Cite
|
Sign up to set email alerts
|

RNA Extraction from Plant Tissue with Homemade Acid Guanidinium Thiocyanate Phenol Chloroform (AGPC)

Abstract: Gene expression studies are a powerful technique to study biological processes, and isolating RNA that is pure, intact, and in sufficient amounts for downstream applications is key. Over the years, the field has moved to the use of commercial kits and ready-made extraction buffers for RNA isolation. This became particularly problematic during the COVID-19 crisis when supply chains were affected and when RNA extraction and analysis reagents were suddenly scarce at a time when they were particularly required. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…Despite these low 260/230 ratio values, all three isolation methods produced RNA that was successfully used for the detection of all targeted graft-transmissible pathogens of citrus using various RT-PCR-based assays without any reaction inhibition (Table 2). Our comparative and regulatory testing results using over 6,000 samples are in agreement with multiple studies that have demonstrated that there is no correlation between 260/230 absorbance ratios of RNA extracts and performance of downstream RT-PCR or RT-qPCR analysis (Figure 2B) (Cicinnati et al, 2008;Ahlfen and Schlumpberger, 2010;Gallagher, 2017;Zepeda and Verdonk, 2022). Specifically for guanidine, it has been calculated that up to 100 mM in an RNA sample does not compromise RT-PCR reactions (Ahlfen and Schlumpberger, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Despite these low 260/230 ratio values, all three isolation methods produced RNA that was successfully used for the detection of all targeted graft-transmissible pathogens of citrus using various RT-PCR-based assays without any reaction inhibition (Table 2). Our comparative and regulatory testing results using over 6,000 samples are in agreement with multiple studies that have demonstrated that there is no correlation between 260/230 absorbance ratios of RNA extracts and performance of downstream RT-PCR or RT-qPCR analysis (Figure 2B) (Cicinnati et al, 2008;Ahlfen and Schlumpberger, 2010;Gallagher, 2017;Zepeda and Verdonk, 2022). Specifically for guanidine, it has been calculated that up to 100 mM in an RNA sample does not compromise RT-PCR reactions (Ahlfen and Schlumpberger, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Specifically for guanidine, it has been calculated that up to 100 mM in an RNA sample does not compromise RT-PCR reactions (Ahlfen and Schlumpberger, 2010). Therefore in the case of RNA isolation from citrus tissues using guanidine, the 260/230 absorption ratios should be used as a complimentary RNA purity measurement, and should never be used as a major determinant of a sample's suitability for pathogen testing using RT-PCR and RT-qPCR based assays (Zepeda and Verdonk, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the method works well with multiple tissues and plants species, different protocols are recommended for seeds (not tested yet with the CiAR method, e.g., see Oñate‐Sánchez & Vicente‐Carbajosa, 2008) or to obtain larger quantities of RNA (see Holding et al., 2007; Reyes et al., 2011; see Current Protocols article; Zepeda & Verdonk, 2021).…”
Section: Commentarymentioning
confidence: 99%